ANALISIS KINERJA MAHASISWA DALAM PENDAMPINGAN IBU HAMIL RISTI DI KOTA SEMARANG TAHUN 2014 - Dea Amarilisa Adespin; Sri Achadi Nugraheni; Cahya Tri Purnami (Media Medika Muda, 2016)
Background: Maternal Mortality Rate (MMR) in Semarang is one of the top five highest MMR in Central Java.As the effort to decrease MMR, Public Health Service (DKK) of Semarang had been colaborated with educational institution to envolved the midwifery student for mentoring high risk mother. Initial studies showed that the program did not work effectively. The objectives of this study was to analyze performance and to find out factors that related to midwivery student’s performance on mentoring high risk mother.Methods: This is a quantitative study used cross sectional design which envolved 115 respondents in Semarang.Data were collected by conducting interview using a structured questionnaire to analyze performance and related factors (knowledge, institution, location of duty, reward, supervision, facilities, attitude, and motivation).  Data were analyzed by using Rank spearman, Chi square and Logistic Regression.Results: This study showed that most of the respondents were good on knowledge (50.4%), perception of reward (60.9%), supervision (59.1%), facilities (58.3%), attitude (66.1%), motivation (89.6%) and performance (53.9%). The results of bivariate analysis showed that knowledge (0.001), reward (p=0.001), supervision (p=0.001), facilities (p=0.002), attitude (p=0.001) and motivation (p=0.001) had positive association with midwivery student’s performance on mentoring high risk mother. Meanwhile, institution (p=0.741) and location of duty (p=0.933) had no association with student performance. Furthermore, the result of multivariate analysis demonstrated that supervision, facilities and attitute jointly influenced midwivery student’s performances on mentoring high risk mother.Conclusion: There were positive relationship between performance with knowledge, reward, supervision, facilities, attitude and motivation.Keywords: Performances, Mentoring, High risk